2019
DOI: 10.22194/jgiass/7.838
|View full text |Cite
|
Sign up to set email alerts
|

DETERMINATION OF GRAIN YIELD AND LEAF CHLOROPHYLL CONTENT OF SOME DRY BEAN (Phaseolus vulgarıs L.) VARIETIES

Abstract: This study was conducted to determine grain yield and leaf chlorophyll content of some dry bean varieties in several growing periods in the Konya ecological conditions. The cultivars included were Akman-98, Goksun, Goynuk-98, Karacasehir-90, Noyanbey-98, Onceler-98, Yunus-90 and Zulbiye. The experiments were set up according to Randomized Block Design with 3 replicates through the dry bean growing periods (May-Oct.) of the years 2012-13 in Bahri Dağdas International Agricultural Research Institute Experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Dry matter and crude fat were determined using the protocol of AOAC (1995). The resulting values were used to calculate the DM and crude fat digestiblities as described in the recent studies (Anjum et al, 2019; Keles et al, 2019;Sharif et al, 2018;Tiwana et al, 2019;).…”
Section: Nutrient Digestibilities Determinationmentioning
confidence: 99%
“…Dry matter and crude fat were determined using the protocol of AOAC (1995). The resulting values were used to calculate the DM and crude fat digestiblities as described in the recent studies (Anjum et al, 2019; Keles et al, 2019;Sharif et al, 2018;Tiwana et al, 2019;).…”
Section: Nutrient Digestibilities Determinationmentioning
confidence: 99%
“…Likewise, chlorophyll content showed no correlation with yield. This could be due to morpho-logical differences in these cultivars; there are slight changes in time for each phenological stage per cultivar, as indicated by Keles et al [45], who found the highest correlation of SPAD with yield in the flowering stage, but not in later stages (R 2 = 0.07 ns).…”
Section: Discussionmentioning
confidence: 89%
“…Dry matter and crude fat were determined using the protocol of AOAC (1995). The resulting values were used to calculate the DM and crude fat digestibility as described in recent studies (Hussain et al, 2018;Sharif et al, 2018;Anjum et al, 2019;Keles et al, 2019;Tiwana et al, 2019).…”
Section: Nutrient Digestibilities Determinationmentioning
confidence: 99%